Restricción del flujo sanguíneo en la funcionalidad de rodilla para pacientes posquirúrgicos de 20 a 35 años que acuden al Centro de Rehabilitación Fisioterapia y kinesiología -Riobamba. Periodo septiembre diciembre 2024. - Aucatoma Ruiz, Leydi Silvana (2025)
Background: Blood flow restriction (BFR), originally developed in Japan as "Kaatsu training," has evolved into an effective rehabilitation strategy. Recent studies highlight its efficacy in postoperative knee recovery, improving strength and functionality with low loads, while also reducing postoperative pain and inflammation. Objective: To determine the effect of blood flow restriction on knee function after knee joint surgery in patients between 20 and 35 years of age attending the physiotherapy and kinesiology rehabilitation center -Riobamba. Methodology: This quantitative, quasi-experimental study assessed the effectiveness of blood flow restriction in knee rehabilitation. A total of 19 patients aged 20 to 35 years were studied. The Lysholm questionnaire and an eight-session treatment protocol were applied, analyzing improvements in postoperative functionality. Results: The sample had a mean age of 26.84 years, with a predominance of males (68.4%). Initially, all patients exhibited poor functionality (<65). After the intervention, 70% of ligament surgeries achieved good functionality. The Wilcoxon test indicated a significant improvement (p<0.05). Conclusion: The initial assessment revealed deficient functionality, emphasizing the importance of the Lysholm scale. Blood flow restriction optimized muscle recovery and significantly improved knee functionality, establishing itself as an effective alternative within the therapeutic protocol.